Angiotensin-II-derived reactive oxygen species on baroreflex sensitivity during hypertension: new perspectives - Queiroz, Thyago M.; Monteiro, Matheus M.; Braga, Valdir A. (Frontiers in Physiology, 2013)
Hypertension is a multifactorial disorder which has been associated with the reduction in baroreflex sensitivity and autonomic dysfunction. Several studies have revealed that increased reactive oxygen species (ROS) generated by nicotinamide adenine dinucleotide phosphate [NAD(P)H] oxidase, following activation of type 1 receptor (AT1R) by Angiotensin-(Ang) II, the main peptide of the Renin–Angiotensin–Aldosterone System (RAAS), is the central mechanism involved in Angiotensin-II-derived hypertension. In the present review we will discuss the role of Angiotensin-II and oxidative stress in hypertension, the relationship between the baroreflex sensitivity (BRS) and the genesis of hypertension and how the oxidative stress triggers baroreflex dysfunction in several models of hypertension. Finally, we will describe some novel therapeutic drugs for improving the baroreflex sensitivity during hypertension.